Productivity of Islamic and Conventional Banks of Malaysia: An Empirical Analysis - Rossazana, Ab. Rahim; Farhana, Ismail (Elsevier, 2013)
The paper presents the productivity change of Malaysian banks for the period 2006-09 by employing Malmquist productivity index. The results reveal that throughout the study period, the productivity of Islamic banks (10.4%) was higher than that of the conventional banks (0.9%). Also, on an average, productivity across Malaysian banking industry increased at an annual rate of 5.4%, which was mainly due to technical change rather than efficiency change. Therefore, this study suggests that Malaysian commercial banking industry can further increase its total factor productivity by improving its efficiency component.